Computerspillets interaktive dramaturgi - Ertløv Hansen, Ole (Peripeti, 2021)
Ertløv Hansen rethinks the classic narrative terms of ‘syuzhet’ and ‘fabula’, as understood in film theory, into the domain of computer games and accounts for the ways in which the terms can lead to a deepened understanding of the interplay between game and gamer.